O ensino de língua inglesa com aplicativos móveis: uma proposta pedagógica para professores de língua inglesa em uma escola municipal na cidade de Rosário/MA - SANTOS, Sabrina Lima dos (2023)
The research deals with the use of mobile applications as a teaching resource in English language classes in the final years of elementary school. The general objective is to analyze the use of mobile applications by teachers in the English language teaching process. The problem was outlined based on the following question: how does the use of mobile applications contribute to the English language teaching process in the final years of elementary school? The methodology adopted was the Case Study using a qualitative approach, exploratory and descriptive in nature. The data collection instrument was interviews carried out with the help of the WhatsApp application. The theoretical framework is based on the use of mobile applications in education (MORAIS, 2003; VIEIRA, 1999), teacher training for the use of technology (PAIVA, 2013; BARAN, 2014), the concept of learning with mobility or M- Learning (CARVALHO, 2015; BARCELOS; TAROUCO; BERCHT, 2009), the use of mobile applications in teaching English (ZARDINI, 2009; PAIVA, 2017), history, definition, identification of the underlying language concept, teaching method used in the development of oral comprehension, speaking, reading, writing, vocabulary and encouraging interaction with mobile applications (VERA, 2017; NEULS, 2015). The results obtained in the research indicate that not all teachers have training in Literature – English, nor have continued training in the area. Regarding technology mastery, they are mostly in the basic range. In relation to the appropriation of digital technologies, many of the teachers did not have training promoted by the Municipal Department of Education (SEMED) to master the technologies. The research product was an E-book with a discussion on how to use the M-Learning methodology in English language classes and the presentation of tutorials on how to use mobile applications in English language classes with the aim of demonstrating the benefits of using of the M-Learning methodology in the English language teaching-learning process to be used by teachers at the Maria José Macau Integrated Unit in the municipality of Rosário (MA).